Assessment of the mechanical properties and water stability of nano-Al2O3 modified high ductility magnesium potassium phosphate cement-based composites. (March 2022) - Feng, Hu; Zhu, Pengfei; Guo, Aofei; Cheng, Zhanqi; Zhao, Xiangyu; Gao, Danying
Abstract: The large-scale application of high ductility magnesium potassium phosphate cement-based composites (HDMPKC) is limited by the poor stability of magnesium potassium phosphate cement (MKPC) in water or a humid environment. Nano-Al2 O3 (NA) was incorporated into the HDMPKC to improve its water stability. The effects of NA content on the workability, compressive strength, flexural behavior, and water stability of the HDMPKC were examined. The results showed that compared with the HDMPKC without NA, 2–6% NA had little effect on the workability; when the NA content was less than 8%, the compressive strength, cracking strength, flexural strength, ductility index, and toughness index were significantly improved. Meanwhile, the NA could improve the strength retention rate, ductility index retention rate, and toughness index retention rate of the HDMPKC that are more than 100%, slightly lower than 100%, and around 100%, respectively, indicating an improved water stability. The scanning electron microscopy results showed that for the matrix with NA, the surface was smooth, and the structural integrity was relatively good, with fewer cracks, which prevented water from entering the matrix and thus resulted in good water stability. Moreover, the NA could improve the bonding between the matrix and fibers, improving the mechanical properties of the HDMPKC. Graphical Abstract: ga1 Highlights: Effect of NA on the workability of the HDMPCC was examined. Effect of NA on the compressive strength of the HDMPCC was examined. Effect of NA on the flexural behavior of the HDMPCC was examined. Effect of NA on the water stability of the HDMPCC was discussed. SEM was conducted to examine the microstructure of the HDMPCC.